THE PHILOSOPHICAL AND CULTURAL PARADIGM OF UKRAINIAN OCCIDENTALISM IN THE LITERARY DISCOURSE OF MUR - Kurinna, Nataliya (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Formulation of the problem. The intensification of the study of the phenomenon of Occidentalism in the scientific academic space is primarily related to the political background - the creation of the state and nation of Ukraine in accordance with the European integration vector, especially in the era of social changes (revolutions, riots, wars) and "passionate outbursts". Occidentalism as a democratic, philosophical-cultural, axiological worldview paradigm, in addition, immanently fulfills the role of a kind of "pendulum" that shakes the imperial and totalitarian regimes. However, the "problem of the West" in the context of geopolitical and geocultural orientation has an interdisciplinary nature, which V. Yaniv drew attention to in his well-known work "Psychological Foundations of Occidentalism", written in 1947-48 as "a boundary problem of general history, sociology, history and philosophy of culture, national psychology or philosophical anthropology, political theory, pedagogy, etc., and it even stands on the borderline of journalism" [22, p.2]. As we can see, the relevance of this problem is surprisingly acute even in the 21st century, especially when it comes to Ukrainian literature, in which Europeanism is considered as one of the methodological problems of national modernization and integration into the world cultural space in the direction of Western culture. Actually, the purpose of the article is to analyze the literary discursive practice of Ukrainian Occidentalism in the domestic scientific dimension, in particular, the period of the MUR. The author elucidates the specifics of Occidentalism of this period, the main philosophical and aesthetic vectors of its development, related to the then emigration cultural continuum, society, politics, ideology, the consciousness of the "DI-PI planets" (U. Samchuk), etc. Research methods: cultural-historical, comparative-historical, systemic, typological, biographical, historiosophical, anthropological approach. The scientific novelty of the article lies in the fact that the specifics of Ukrainian Occidentalism in the discourse of MUR, which, according to its philosophical and aesthetic principles, was a priori aimed at the development of the Ukrainian literature of the European genre with the preservation of national identity and self-identity became the subject of a separate study. The practical significance is that the main provisions and conclusions of the article can be used for analytical investigations of the European intentions of the Ukrainian intelligentsia, the spiritual national elite in the context of Western European trends in domestic literature and culture, when studying the philosophy and poetics of the literature of the Ukrainian diaspora of the 20th century, a conceptual approach to the study of Ukrainian Occidentalism in literary discourse, as well as for post-colonial studies.